Computation of Electromagnetic Properties of Molecular Ensembles. Issue 9 (9th April 2020) - Fernandez‐Corbaton, Ivan; Beutel, Dominik; Rockstuhl, Carsten; Pausch, Ansgar; Klopper, Wim
Abstract: We outline a methodology for efficiently computing the electromagnetic response of molecular ensembles. The methodology is based on the link that we establish between quantum‐chemical simulations and the transfer matrix (T‐matrix) approach, a common tool in physics and engineering. We exemplify and analyze the accuracy of the methodology by using the time‐dependent Hartree‐Fock theory simulation data of a single chiral molecule to compute the T‐matrix of a cross‐like arrangement of four copies of the molecule, and then computing the circular dichroism of the cross. The results are in very good agreement with full quantum‐mechanical calculations on the cross. Importantly, the choice of computing circular dichroism is arbitrary: Any kind of electromagnetic response of an object can be computed from its T‐matrix. We also show, by means of another example, how the methodology can be used to predict experimental measurements on a molecular material of macroscopic dimensions. This is possible because, once the T‐matrices of the individual components of an ensemble are known, the electromagnetic response of the ensemble can be efficiently computed. This holds for arbitrary arrangements of a large number of molecules, as well as for periodic or aperiodic molecular arrays. We identify areas of research for further improving the accuracy of the method, as well as new fundamental and technological research avenues based on the use of the T‐matrices of molecules and molecular ensembles for quantifying their degrees of symmetry breaking. We provide T‐matrix‐based formulas for computing traditional chiro‐optical properties like (oriented) circular dichroism, and also for quantifying electromagnetic duality and electromagnetic chirality. The formulas are valid for light‐matter interactions of arbitrarily‐high multipolar orders. Abstract : We outline a methodology for efficiently computing the electromagnetic response of molecular ensembles. Instead of performing quantum‐mechanical simulations of the entire ensemble, we combine the quantum‐mechanical simulations of single molecules with the transfer matrix (T‐matrix) approach, a common tool in physics and engineering. We show that the T‐matrix calculations agree very well with the full quantum‐mechanical calculations. We also show how the methodology can be used to predict experimental measurements on a molecular material of macroscopic dimensions.